HUBUNGAN PERILAKU NEGATIF PASIEN DAN KELUARGA TERHADAP STRES KERJA PERAWAT - Ratnasari Ratnasari (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
In Indonesia, negative behavior of patients with violence against work among nurses was reported as physical assault, verbal, sexual violence, incidents, and legal threats which were mostly carried out by patients and their families. The negative impacts that arise include nurses feeling depressed, feeling like avoiding patients, being less enthusiastic about work, and stress arising. The purpose of this study was to determine the relationship between negative behavior of patients and their families on the work stress of nurses. The research method used is cross sectional. The population of this study were all nurses in the inpatient room. The number of samples is 33 respondents. The sampling technique used is simple random sampling. Data collection using the Perceptions of Prevelence of Aggression Scale (POPAS) questionnaire in Indonesian (Elita et al, 2011) and work stress. Data analysis method using gamma somers’d. The results of the analysis obtained a p value of 0.000 (<0.05) meaning that there was a negative relationship between patient and family on work stress with a positive correlation direction of 0.741 which means the higher the negative behavior of nurses